Cash Management: A Case Study of logs & lumber Ltd, Kumasi - Osman, Halidu Babamu (2014)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirement for the award of Master of Business Administration (Accounting)